PROBLEM BASED LEARNING DENGAN MATHCITYMAP UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Shofura Khaudhiya Zain; Adi Nur Cahyono (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by students' low mathematical problem-solving abilities and the lack of utilization of interactive technology relevant to contextual objects around the school environment. The focus of the problem is directed at testing the validity, practicality, and effectiveness of the Problem Based Learning (PBL) model assisted by the MathCityMap application on the material of linear equations and inequalities with one variable. Adopting the Development Research method with a 4-D model, the study implementation flow is systematically constructed including the define, design, develop, and disseminate stages. Data were collected through problem-solving ability test instruments referring to the four stages of Polya, validation sheets, and user response questionnaires that were processed descriptively and inferentially. The research findings confirm the product's very good validity level with a module score of 97.86 percent and media of 97 percent, while the practicality test reached 88 percent. In terms of performance, this integration has proven effective in boosting academic results based on the average posttest achievement of 79.30 which successfully exceeded the actual completion limit of 64.90 and the pretest of 58.05. The significance of the influence was strengthened by a paired t-test with a p-value of less than 0.001 accompanied by the achievement of classical completeness above 75 percent. The main conclusion confirms that the PBL syntax assisted by MathCityMap is valid, practical, and effective in improving students' tactical numerical problem-solving skills in the moderate improvement category. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemecahan masalah matematis siswa serta kurangnya pemanfaatan teknologi interaktif yang relevan dengan objek kontekstual di sekitar lingkungan sekolah. Fokus masalah diarahkan pada pengujian kevalidan, kepraktisan, serta keefektifan model Problem Based Learning (PBL) berbantuan aplikasi MathCityMap pada materi persamaan dan pertidaksamaan linear satu variabel. Mengadopsi metode Development Research dengan model 4-D, alur pelaksanaan studi dikonstruksikan secara sistematis meliputi tahap define, design, develop, dan disseminate. Data dihimpun melalui instrumen tes kemampuan problem solving merujuk pada empat tahapan Polya, lembar validasi, serta angket respon pengguna yang diolah secara deskriptif dan inferensial. Temuan riset mengonfirmasi tingkat kevalidan produk sangat baik dengan skor modul 97,86 persen serta media 97 persen, sementara uji kepraktisan menyentuh angka 88 persen. Secara performa, integrasi ini terbukti efektif mendongkrak hasil akademis berdasarkan raihan rata-rata posttest sebesar 79,30 yang sukses melampaui batas tuntas aktual 64,90 serta pretest sebesar 58,05. Signifikansi pengaruh diperkuat oleh uji t berpasangan dengan nilai p kurang dari 0,001 disertai pencapaian ketuntasan klasikal di atas 75 persen. Simpulan utama menegaskan bahwa sintaks PBL berbantuan MathCityMap valid, praktis, dan efektif meningkatkan kecakapan taktis pemecahan masalah numerik siswa pada kategori peningkatan sedang.